PENGARUH BUDAYA SEKOLAH TERHADAP KOMPETENSI PRODUKTIF PESERTA DIDIK SMK NEGERI SUMATERA BARAT - Ramli . (LPMPP Universitas Negeri Yogyakarta, 2013)
Abstrak: Penelitian ini bertujuan untuk melihat tingkat capaian (1) budaya Sekolah Menengah Kejuruan; (2) kompetensi produktif peserta didik SMK; dan (3) pengaruh budaya sekolah terhadap kompetensi produktif peserta didik SMK Sumatera Barat. Metode penelitian yang digunakan deskriptif kuantitatif, populasi sebanyak 2929 orang peserta didik, sampel dipilih sebanyak 160 orang dengan teknik multistage random sampling. Data dikumpulkan dengan angket dan dokumentasi. Analisis data menggunakan teknik deskriptif dan inferesial. Penelitian ini menemukan (1) budaya sekolah SMK termasuk kategori baik; (2) kompetensi produktif peserta didik termasuk kategori baik; dan (3) terdapat pengaruh positif yang signifikan budaya sekolah terhadap kompetensi produktif peserta didik SMK Negeri Sumatera Barat sebesar 12,7%. Kata Kunci: budaya sekolah, kompetensi produktif, peserta didik THE EFFECT OF THE SCHOOL CULTURE ON THE PRODUCTIVE COMPETENCIES OF WEST SUMATRAN VOCATIONAL SCHOOL STUDENTS Abstract: This study was aimed to reveal the achievement level of (1) the culture of vocational schools; (2) the productive competencies of vocational school students; and (3) the effect of school culture on productive competencies of West Sumatran vocational school students. The study used is the descriptive quantitative method. the number of population was 2929 students. The sample, consisting of 160 students, was taken by using the multistage random sampling technique. The data, collected using a questionnaire and documentation, were analyzed using the descriptive and inferential analyses. The study found that: (1) the culture of vocational school was in the good category; (2) productive competencies of students were in the good category; and (3) there was a positive and significant influence of the school culture on the productive competencies of West Sumatran vocational school students by 12.7%. Keywords: school culture, productive competencies, students